Implementasi Algoritma AES, ElGamal, dan SHA3 untuk Keamanan File Digital - Joshua Allan Saputra; Justinus Andjarwirawan; Lily Puspa Dewi (Jurnal Infra, 2021)
In this modern era, technological developments in the world are developing very quickly. This very rapid technological advancement makes work and exchange of data and information very fast, accurate, and efficient. But with this convenience, new security gaps have also emerged, such as the emergence of crimes in cyberspace (cyber-crime). These actions can be in the form of data theft, breaking someone's password, to distributing software or someone's data without permission. Therefore, this study aims to overcome these security problems by implementing the AES algorithm, ElGamal algorithm, and SHA3 hash function so that they can be used simultaneously to become a secure and solid encryption system.The testing in this study is divided into three stages, namely testing the system's ability to perform the encryption and decryption process, testing the system speed, and testing the web platform. From the test results, it can be proven that the program can encrypt and decrypt all types of files properly and can detect the authenticity of the file. In web testing, it can be seen that the web is able to send encrypted files to recipients properly without missing anything.This research produces a software that can perform encryption and decryption of various types of files and can verify if there are changes / modifications to the file. This research also produces a web platform that can be used to send files between users correctly.From the test results, the program can encrypt files with an average speed of 999.43 bytes/ms and decrypt files with an average speed of 450.38 bytes/ms.